Studi Kasus Kesalahan Penulisan Surat Dinas di Lingkungan Kominfo Palembang - Siti Anisyah; Ayu Puspita Indah Sari (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2025)
The correct writing of official letters in accordance with the rules is an important element in official communication within government agencies. However, various writing errors that can disrupt understanding and negatively impact the agency's image are often encountered. This study aims to identify and analyze the writing errors that occur in official letters at the Communication and Information Office of South Sumatra Province. The method used in this research is descriptive analysis with a qualitative approach, where data collection is obtained through observation and documentation. The results of the study indicate that common writing errors include mistakes in grammar, spelling, and the use of inappropriate terms. Additionally, a lack of understanding regarding the rules of writing official letters among employees is also one of the contributing factors. It is hoped that this research can provide recommendations to improve the quality of official letter writing through training and socialization regarding proper writing rules, so that official communication in the Communication and Information Office of South Sumatra Province can be conducted more effectively and professionally. Kata Kunci: Kualitatif, Dokumentasi, Kesalahan Penulisan, Tata Bahasa